MENELAAH MAKNA GERAKAN TARI KERAMBA APUNG DI DESA ARO KECAMATAN MUARA BULIAN KABUPATEN BATANG HARI - Destrinelli; Annisa Amalia; Mei Seven Panjaitan; Alfina Febrianti; Pinta Uli Panjaitan; Andre Pratama Sitepu; Assalwa Tazkia L; Hania Dwitri Fadhia; Natasya Agustin; Cindi Sandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the meaning of the Keramba Apung dance movements in Aro Village, Muara Bulian District, Jambi. This study is a qualitative descriptive study. The data consists of primary data and secondary data. Data collection techniques with direct observation, interviews, and documentation. while data analysis is carried out through data collection, analyzing and describing and drawing conclusions. The results of the study indicate that the Keramba Apung dance is a traditional dance that grows and develops in Aro village. This dance is often used in traditional ceremonies, or welcoming guests. This dance describes the character of the Aro Village community, namely hard workers, helping each other and working together. In the Keramba Apung dance there are several types of movements that have meaning in each movement, namely; such as the Canon Movement as a depiction of the happiness and joy of the community when working together to make floating cages, the Broken movement as a depiction of working together/working together to make floating cages or working together when the fish harvest arrives, meaningful movements in the form of the Hand movement on the chest and gracefully downwards as a depiction of gratitude to Allah SWT, and the Closing Worship movement as a depiction of respect. The Floating Cage Dance is a reflection of the Aro village community carrying out fish cultivation up to harvesting fish in the Floating Cage